Part II: The Chicago Course. Issue 6 (18th August 2019) - Dobson, Marcia D-S.; Riker, John H.
ABSTRACT: Part II offers an understanding of how unusual, creative, and meaningful the course taught at the Chicago Institute is. Chapter 1 explains how the course came into existence and outlines its structure, along with giving a syllabus for the course. Chapter 2 is probably the essence of this issue of the journal, as it gives detailed student responses to the analysts' presentations. Chapter 3 details the student responses to one class in particular, a special class on Allen Siegel's book, Heinz Kohut and the Psychology of the Self, at Allen's house in which he addresses questions raised by the students about the book in particular and self psychology in general.